High Level of Soluble CD146 In Cerebrospinal Fluid Might be a Biomarker of Severity of Anti-N-Methyl-D-Aspartate Receptor Encephalitis - Li, Qing; Chen, Jinglong; Yin, Mengzhuo; Zhao, Jun; Lu, Fuchang; Wang, Zhanhang; Yu, Xiaoqi; Wang, Shuangyan; Zheng, Dong; Wang, Honghao (Frontiers in Immunology, 2021)
Background Disruption of the blood–brain barrier (BBB) is an important pathophysiological process of anti-N-methyl-D-aspartate receptor (anti-NMDAR) encephalitis. A recent multi-center study showed that soluble (s) CD146 is a potential biomarker for monitoring early BBB damage and central nervous system inflammation, but little is known about sCD146 in anti-NMDAR encephalitis. Method Twenty-three anti-NMDAR encephalitis patients and seventeen controls with non-inflammatory neurological diseases were recruited. sCD146 and inflammatory cytokines in cerebrospinal fluid (CSF) and serum were detected by ELISA. Modified Rankin scale (mRS) scores were used to assess the neurological status of each patient. A follow-up review was completed three months after discharge. Results sCD146 levels in the CSF of patients with the acute stage anti-NMDAR encephalitis were significantly increased compared with controls and accompanied by increases in TNF-α, IL-6 and IL-10. CSF sCD146 was positively correlated with neuroinflammatory factors in the CSF and with mRS score. Three months after effective treatment, CSF sCD146 in patients was significantly decreased but remained significantly different compared with the controls. Conclusion Our data suggested that higher expression of CSF sCD146 correlated with more serious neurological damage. Therefore, levels of CSF sCD146 may represent a promising indicator for monitoring disease and optimizing clinical treatment decisions in the early stages of anti-NMDAR encephalitis.